Family food practices: relationships, materiality and the everyday at the end of life. Issue 2 (21st February 2018) - Ellis, Julie
Abstract: This article draws on data from a research project that combined participant observation with in‐depth interviews to explore family relationships and experiences of everyday life during life‐threatening illness. In it I suggest that death has often been theorised in ways that make its 'mundane' practices less discernible. As a means to foreground the everyday, and to demonstrate its importance to the study of dying, this article explores the (re)negotiation of food and eating in families facing the end of life. Three themes that emerged from the study's broader focus on family life are discussed: 'food talk' and making sense of illness; food, family and identity; and food 'fights'. Together the findings illustrate the material, social and symbolic ways in which food acts relationally in the context of dying, extending conceptual work on materiality in death studies in novel directions. The article also contributes new empirical insights to a limited sociological literature on food, families and terminal illness, building on work that theorises the entanglements of materiality, food, bodies and care. The article concludes by highlighting the analytical value of everyday materialities such as food practices for future research on dying as a relational experience.